A Genealogy of Cultural Politics, Identity and Resistance: Reframing the Māori–Pākehā binary. Issue 2 (June 2013) - Bidois, Vaughan
Over the past four decades in Aotearoa New Zealand, anti-colonial and postcolonial theories have been engaged to analyse the historical and contemporary conditions of the Indigenous peoples of the land. As a result, dualist and oppositional comparisons of identity, knowledge and understanding have been utilized to frame the (post)colonial experience between Māori and Pākehā. This article applies a Foucauldian analysis of the colonial binary and the implications for Māori and Pākehā subjectivities, cultural identity and relations today. Foucault's genealogy analyses and uncovers the historical relationship between truth, knowledge and power, and so provides a critique of conventional thinking and practices that are positioned within a traditional "Self and Other" binary of power. This article explores the possibility of reframing traditional Māori and Pākehā oppositional cultural politics; a cultural frame that centres on the notion of the "ethical subject" and a conceptual space that seeks to operate beyond the Self–Other binary.